A table of derivatives on arbitrary time scales - Torres, D. F. M. (2017)
This paper presents a collection of useful formulas of dynamic derivatives on time scales, systematically collected for reference purposes. As an application, we define trigonometric and hyperbolic functions on time scales in such a way the most essential qualitative properties of the corresponding continuous functions are generalized in a proper way.